Serotonergic neurons in the nucleus raphe obscurus contribute to interaction between central and peripheral ventilatory responses to hypercapnia - da Silva, Glauber S. F.; Giusti, Humberto; Benedetti, Mauricio; Dias, Mirela B.; Gargaglioni, Luciane H. [UNESP]; Branco, Luiz Guilherme S.; Glass, Mogens L. (Springer, 2011)
Serotonergic (5-HT) neurons in the nucleus raphe obscurus (ROb) are involved in the respiratory control network. However, it is not known whether ROb 5-HT neurons play a role in the functional interdependence between central and peripheral chemoreceptors. Therefore, we investigated the role of ROb 5-HT neurons in the ventilatory responses to CO2 and their putative involvement in the central-peripheral CO2 chemoreceptor interaction in unanaesthetised rats. We used a chemical lesion specific for 5-HT neurons (anti-SERT-SAP) of the ROb in animals with the carotid body (CB) intact or removed (CBR). Pulmonary ventilation (V (E)), body temperature and the arterial blood gases were measured before, during and after a hypercapnic challenge (7% CO2). The lesion of ROb 5-HT neurons alone (CB intact) or the lesion of 5-HT neurons of ROb+CBR did not affect baseline V (E) during normocapnic condition. Killing ROb 5-HT neurons (CB intact) significantly decreased the ventilatory response to hypercapnia (p < 0.05). The reduction in CO2 sensitivity was approximately 15%. When ROb 5-HT neurons lesion was combined with CBR (anti-SERT-SAP+CBR), the V (E) response to hypercapnia was further decreased (-31.2%) compared to the control group. The attenuation of CO2 sensitivity was approximately 30%, and it was more pronounced than the sum of the individual effects of central (ROb lesion; -12.3%) or peripheral (CBR; -5.5%) treatments. Our data indicate that ROb 5-HT neurons play an important role in the CO2 drive to breathing and may act as an important element in the central-peripheral chemoreception interaction to CO2 responsiveness.
Keywords: Central chemoreception; Peripheral chemoreception; Hypercapnia; Pulmonary ventilation; 5-HT neurons; Medullary raphe